2006
DOI: 10.1088/0268-1242/21/6/007
|View full text |Cite
|
Sign up to set email alerts
|

A surface optical phonon assisted transition in a semi-infinite superlattice with a cap layer

Abstract: Using the transfer matrix method and Fermi's golden rule, we calculate the intersubband transition rates between surface electronic states due to different surface optical phonon modes (SOPMs) for a semi-infinite superlattice (SL) with a cap layer in the dielectric continuum approximation. The influence of various structural configurations on surface electron-phonon scattering is given in detail. The calculated results show that the surface electron-phonon scattering rates are markedly influenced by the magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…On the other hand, room temperature resonant Raman scattering has been reported to probe the electronic state in CdS nanowires by matching the excitation energy with the band gap of CdS . Electron−phonon interaction has a vital influence on the electronic properties and optical properties of semiconductor nanomaterials and is of great importance for device applications . Here, we investigate the effect of laser power on the particle size evolution in CdS nanocrystals by Raman spectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, room temperature resonant Raman scattering has been reported to probe the electronic state in CdS nanowires by matching the excitation energy with the band gap of CdS . Electron−phonon interaction has a vital influence on the electronic properties and optical properties of semiconductor nanomaterials and is of great importance for device applications . Here, we investigate the effect of laser power on the particle size evolution in CdS nanocrystals by Raman spectroscopy.…”
mentioning
confidence: 99%
“…8 Electron-phonon interaction has a vital influence on the electronic properties and optical properties of semiconductor nanomaterials and is of great importance for device applications. 9 Here, we investigate the effect of laser power on the particle size evolution in CdS nanocrystals by Raman spectroscopy. Laser-power-induced multiphonon resonant Raman scattering in the localized area in CdS nanocrystals has also been reported in detail, and a theoretical temperature dependent band gap has been employed to understand multiphonon resonance.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] On the other hand, one interesting kind of lattice vibration can be localized on the surfaces of nanostructures, leading to a frequency intermediate between the transverse and longitudinal optical (TO and LO) phonon modes. 8,9 Such phonon mode is usually called the surface optical (SO) phonon mode which could be observed when the translational symmetry of the surface potential is broken, i.e., surface roughness or construction of a grating. 10 For the SO phonon modes, experimental observations have been reported in GaP and ZnS nanostructures.…”
mentioning
confidence: 99%
“…[11][12][13] However, there are few reports on the SO phonon mode in the technologically important InGaN/ GaN MQWs structures which are commonly used as active layers in short-wavelength light-emitting devices. 8,[14][15][16] In this letter, we report an investigation of the SO phonon modes in the InGaN/GaN MQW nanopillars with different diameters by using scanning confocal micro-Raman spectroscopy/microscopy. The observed SO phonon frequency shows a distinct depend on the size of the nanopillars, which is consistent with the calculation result.…”
mentioning
confidence: 99%
“…[3][4][5][6] The electron-optical phonon interaction influences the electronic and optical properties of semiconductor nanomaterials and is greatly important for device applications. 7 A way to increase the luminescence efficiency of semiconductor nanoparticles was reported by Bhargava et al 8 They demonstrated that ZnS nanoparticles doped with luminescent ions ͑Mn 2+ ͒ exhibit a high luminescence efficiency. They also showed that by incorporating an impurity in a quantum-confined structure, the dominant recombination route can be transferred from the surface states to the impurity states, thus significantly increasing the luminescence efficiency.…”
mentioning
confidence: 99%